Inovação, concorrência e crescimento empresarial: teoria e política aplicadas à indústria de fitoterápicos no Brasil - Lima, Semíramis Mangueira de (2011)
The study concerns the analysis of productive development policies in Brazil using, based on theory neochumpeterianas and evolutionary. To this demonstrates the importance of innovation, competition and regulation for the formulation of a path of business growth for domestic industries, identifying innovative strategies that further this growth and the possible trajectories that such growth might adopt. As an illustration of the impact of innovation, the study verifies the phytotherapy industry as possible to be bolstered by innovation policies in Brazil and the development of the sector could boost national growth. Innovation is the development of new products, services, techniques or improving existing production methods, the adaptation of technologies developed successful. The introduction of innovation increases competition and hence profits, leading to business growth. The phytotherapy has the potential to be the technological paradigm that will lead Brazil to approach the world technological frontier and thus enable the development of Brazil, with increased income and employment through the strengthening of the domestic industry.